Analisis Butir Soal Tes Pemecahan Masalah Matematika - Pardimin Pardimin; Sri Adi Widodo; Indriyati Eko Purwaningsih (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2017)
The instrument is one of the tools used to collect a data, whether or not a research instrument needs to be seen the characteristics of the instrument being prepared. So the purpose of this research is to know the characteristics of test instruments Problem-solving mathematics that have been compiled on the material geometry for junior high school class VII. The research method used is the basic research method. Data analysis is done qualitatively and quantitatively. Qualitative analysis is used to see the characteristic of content validity, whereas quantitative analysis is done to see the characteristics of differentiating power and instrument reliability. The results show that all items have good content validity and distinguishing power, with a very high degree of reliability.